Clinical evaluation of multiple-surface ART restorations: three-year follow-up - Cefaly, Daniela; Barata, Terezinha de Jesus Esteves; Bresciani, Eduardo [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Navarro, Maria Fidela de Lima (Editora Cubo, 2013)
Objective: To evaluate the performance of multiple-surface restorations made with two different glass-ionomer cements (GICs) using the Atraumatic Restorative Treatment (ART) in permanent teeth. Material and methods: A total of 60 restorations were placed in schoolchildren (9-16 years of age) by two dentists using standard ART procedures. The restorations were randomly divided into two groups. Thirty cavities were filled with high-viscosity GIC (Ketac Molar-3M ESPE) and 30 cavities were filled with resin-modified GIC (Fuji VIII-GC Corp.). Two calibrated independent examiners carried out the evaluation according to ART criteria. Data were statistically analyzed using multiple logistic regression models to evaluate the variables associated with the success (GIC, operator, Class type). The 95% confidence intervals (CI) for success were based on the binomial distribution. A difference was statistically significant if p<0.05. Results:In a 3-year follow-up, 57 restorations were evaluated. In the Ketac Molar group, 3 restorations were not evaluated, 21 were considered successful and 6 unsuccessful. In the Fuji VIII group, 28 restorations were considered successful and 2 unsuccessful. The logistic regression model showed that the combination of the variables was only statistically significant in relation to survival of the ART restorations (p=0.036). There were no statistically significant differences between the groups taking each variable into account. The best performance included the combination: Fuji VIII, operator B and Class I involving two or more tooth surfaces. Conclusion: The clinical performance of the multiple-surface ART restorations of both materials was considered satisfactory with a high success rate after 3 years.

Objetivo: Avaliar o comportamento clínico de restaurações de superfícies múltiplas, realizadas com dois cimentos de ionômero de vidro (CIVs) em dentes permanentes, utilizandose o Tratamento Restaurador Atraumático (ART). Material e Métodos: 60 restaurações foram realizadas em escolares (idade entre 9 - 16 anos) por dois dentistas utilizando-se os procedimentos convencionais do AR. As restaurações foram distribuídas aleatoriamente em dois grupos. Trinta cavidades foram restauradas com CIV de alta viscosidade (Ketac Molar - 3M ESPE) e 30, com CIV modificado por resina (Fuji VIII-GC Corp.). Dois avaliadores calibrados e independentes realizaram a avaliação segundo os critérios do ART. Os resultados foram submetidos à análise estatística utilizando-se modelos de regressão logística múltipla, avaliando-se o sucesso em função das variáveis associadas (CIV, operador e tipo de cavidade). Intervalos de confiança de 95% para o sucesso foram baseados na distribuição binomial. Diferenças estatisticamente significantes ocorreram se p < 0,05. Resultados: Em 3 anos de acompanhamento 57 restaurações foram avaliadas. No grupo do Ketac Molar, 3 restaurações não foram avaliadas, 21 obtiveram sucesso e 6 falharam. No grupo do Fuji VIII, 28 restaurações obtiveram sucesso e 2 falharam. A combinação de variáveis foi somente significante em relação à sobrevida das restaurações (p = 0,036). Não houve diferenças entre os grupos considerando-se cada variável independentemente. A combinação apresentando melhor desempenho foi: Fuji VIII, operador B e Classe I envolvendo duas ou mais superfícies dentárias. Conclusão: O desempenho clínico de restaurações de ART de superfícies múltiplas foi considerado satisfatório para ambos os materiais testados, apresentando altos índices de sucesso após três anos.
Avaliação clínica de restaurações de ART de superfícies múltiplas: acompanhamento de três anos
Keywords: Glass-ionomer cements; Atraumatic restorative treatment; Clinical trial; Cimento de ionômero de vidro; Tratamento restaurador atraumático; Esquisa clínica